Trinuclear molybdenum clusters with sulfide bridges as potential anionic receptors via chalcogen bonding. Issue 26 (25th June 2021) - Novikov, Alexander S.; Gushchin, Artem L.
Abstract : Trinuclear Mo3 S7 cluster complexes with sulfide bridges as potential anionic receptors due to chalcogen bonding. Abstract : In this communication, we would like to draw the attention of the scientific community to the potential applicability of various trinuclear Mo3 S7 cluster complexes with sulfide bridges as potential anionic receptors due to chalcogen bonding. The results of the inspection of the CCDC database and DFT calculations of selected model supramolecular associates based on the previously published X-ray structures of [Mo3 S7 (Et2 dtc)3 ]X (X = Cl −, I −, ClO4 −, and SO4 2− ) complexes followed by the topological analysis of electron density distribution within the QTAIM approach and NCI analysis reveal that the Mo3 S7 clusters with bridging sulfide ligands can attract various anions via chalcogen bonding. We believe that this finding may be interesting for the development of smart materials for anion recognition purposes, and corresponding experimental studies will not be long in coming.